2019
DOI: 10.1242/bio.036483
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular characterization and overexpression of mnp6 and vp3 from Pleurotus ostreatus revealed their involvement in biodegradation of cotton stalk lignin

Abstract: Fungal secretory heme peroxidase (Class II POD) plays a significant role in biomass conversion due to its lignin-degrading activity. In this study, genome-wide identification and bioinformatics were performed to analyze P leurotus ostreatus peroxidases ( PoPOD s). A total of six manganese peroxidases (MnPs) and three versatile peroxidases (VPs) were obtained. Bioinformatics analysis and qRT-PCR showed that P. ostreatus mnp6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Genetic modifications of fungal strains in order to improve lignin degradation, restrict carbohydrates loss, raise the growth rate, or increase the optimal growth temperature have the potential to improve the fungal pretreatment process in the future. White-rot fungi have been modified for overexpression of ligninolytic enzymes [106], heterologous expression of lignocellulases [107,108], and avoidance of cellulase production to restrict cellulose loss [32]. Developing new microbial strains that exploit the ligninolytic systems of white-rot fungi, while including benefits of different microorganisms, such as the higher growth rate of bacteria or yeast, could help develop a better platform for the optimization of biological pretreatment.…”
Section: Potential Strategies To Reduce the Sugar Production Costmentioning
confidence: 99%
“…Genetic modifications of fungal strains in order to improve lignin degradation, restrict carbohydrates loss, raise the growth rate, or increase the optimal growth temperature have the potential to improve the fungal pretreatment process in the future. White-rot fungi have been modified for overexpression of ligninolytic enzymes [106], heterologous expression of lignocellulases [107,108], and avoidance of cellulase production to restrict cellulose loss [32]. Developing new microbial strains that exploit the ligninolytic systems of white-rot fungi, while including benefits of different microorganisms, such as the higher growth rate of bacteria or yeast, could help develop a better platform for the optimization of biological pretreatment.…”
Section: Potential Strategies To Reduce the Sugar Production Costmentioning
confidence: 99%
“…Pleurotus spp. are thought to degrade lignin with laccases (LaCs) and manganese dependent peroxidases (MnPs) that they produce ( Knop et al, 2014 ; Xiao et al, 2017 ; Wang et al, 2019b ). However, whether they can produce lignin peroxidases (LiPs) is debatable and has yet to be proven ( Asgher et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the overexpression of the enzyme manganese peroxidase pomnp6 and versatile peroxidase povp3 in P. ostreatus led to higher lignin degradation in cotton stalks. These data suggested that pomnp6 and povp3 might help develop sustainable energy (Wang et al, 2019). Likewise, the protein kinase A catalytic subunit (PKAc) is essential for inducing the wood degradation system in P. ostreatus.…”
Section: Mutants and Overexpression Of Genesmentioning
confidence: 96%